Penerapan Metode Run Out Time (ROT) untuk Perencanaan dan Penjadwalan Produksi Paving Block di CV. XYZ - Rangga Agriyan Purnama Setya; Hilyatun Nuha (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
CV. XYZ is a K300 paving block manufacturer in Sidoarjo that produces five types of products (rectangular, square, hexagonal, three-dimensional, and bishop-shaped) using a make-to-stock system. Differences in demand levels across products lead to inventory imbalances, resulting in some products being at risk of stockouts while others accumulate in excess. This study applies the Run Out Time (ROT) method to determine production priorities and develop a daily production schedule, using actual demand data from May 2024 to April 2026. The results show that ROT produces a dynamic priority sequence, with the most consistent order being: 3-Dimensional/Hexagonal, Square, Rectangular, and Bishop. This method effectively prevents stockouts for all products throughout the 12 planning periods (May 2026–April 2027).